Error Analysis and Numeric Simulation Research of Parallel Seismic Method - Chao Lin; Cheng-Lin Zhang; Li Rao; Chuang Yang; Bin An; Bao–Feng Zhao; Tao Zhan; Xian-Jun Tan (Geofluids)
The parallel seismic method is an effective method to detect the length of pile. In the paper, based on the ray theory of Snell’s law, the two methods of determining the pile length by the first transmission P-wave in the side hole are discussed and modified. The error influencing factors of both two methods are then analysed. Finally, the finite element software ABAQUS was used to simulate the inspection of pile foundations by the parallel seismic method. The numerical simulation results were compared with the results of the error calculation theory to verify the applicability of the error calculation theory. The error calculation theory was then tested and applied in an engineering example. The results show that (1) in order to reduce errors, unreasonable data points need to be removed when fitting the inspection data points and (2) the larger the pile slenderness ratio, the smaller the distance between the side holes and the pile, and the more accurate the pile length results obtained.